Uruguay : Fifth Review Under the Stand-By Arrangement and Requests for Modification of the Arrangement and Waiver of Nonobservance and Applicability of Performance Criteria-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uruguay. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper examines Uruguay's Fifth Review Under the Stand-By Arrangement and Requests for Modification of the Arrangement and Waiver of Nonobservance and Applicability of Performance Criteria. The macroeconomic framework is broadly on track, but progress with structural reform remains uneven. Fiscal performance has been better than programmed, reflecting buoyant revenues. The monetary and balance-of-payments targets of the program have been met. Although program risks have diminished further since the last review, important vulnerabilities remain, leaving no room for policy slippages.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet